Effect of the excess of bismuth on the morphology and properties of the BaBi2Ta2O9 ceramics - Simoes, A. Z.; da Costa, GCC; Ramirez, M. A.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2005)
In this study, the effect of bismuth content on the crystal structure, morphology and electric properties of barium-bismuth-tantalate (BBT) ceramics was explored with the aid of X-ray diffraction (XRD), scanning electron microcopy (SEM), dielectric properties and ferroelectric hysteresis loops. BaBi2Ta2O9 (BBT) ceramics have been successfully prepared by the solid-state reaction. The BBT phase was crystallized at 900 degreesC for 2 h. The excess of bismuth controls the grain size, affecting the density of the material. Measurements of dieletric constant and dieletric losses confirm that the material is a ferroeletric with a Curie temperature around 77 degreesC. The dieletric constant measured at room temperature was 400, with a dielectric loss of 0.03. Both the phase-transition behaviour and ferroelectric properties, such as spontaneous polarization (P-s), showed a dependence on Bi content. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: ceramics; electrical properties; fatigue; sintering